Bu-Shen-Fang-Chuan formula attenuates cigarette smoke-induced inflammation by modulating the PI3K/Akt-Nrf2 and NF-κB signalling pathways. (28th October 2020) - Li, Qiuping; Wang, Guifang; Xiong, Shi Hang; Cao, Yuxue; Liu, Baojun; Sun, Jing; Li, Lulu; Mohammadtursun, Nabijan; Yu, Hua; Dong, Jingcheng; Wu, Jinfeng
Abstract: Ethnopharmacological relevance: Chronic obstructive pulmonary disease (COPD) is a respiratory inflammatory disease. Unlike asthma, COPD is insensitive to glucocorticoid treatment; thus, it is of great importance to find alternative medications, including Chinese medicine, to suppress inflammation. Bu-Shen-Fang-Chuan formula (BSFCF) is commonly used for the treatment of COPD in China. However, the mechanisms of BSFCF in COPD treatment are still unclear. Aim of the study: To verify the anti-inflammatory efficacy of BSFCF in COPD and to explore the possible mechanisms underlying its anti-inflammatory efficacy based on the phosphatidylinositol 3 kinase (PI3K)/protein kinase B (Akt)-Nuclear factor erythroid 2-related factor 2 (Nrf2) and Nuclear factor (NF)-κB signalling pathways. Materials and methods: A rat model of COPD was established by chronic exposure to cigarette smoke (CS) for 6 months. Bronchoalveolar lavage fluid (BALF) and blood were obtained to detect inflammatory cytokines. Lung samples were harvested, and part of each sample was fixed for subsequent H&E staining and immunohistochemical (IHC) analysis. The remaining lung tissues were used for RNA sequencing analysis and western blotting. Results: BSFCF significantly reduced inflammatory infiltration in the lungs of CS-exposed rats and decreased the concentrations of tumor necrosis factor (TNF)-α and interleukin (IL)-6 in both the BALF and serum. Additionally, BSFCF evidently attenuated NF-κB activation and downregulation of glucocorticoid receptor (GR) caused by CS. Furthermore, BSFCF increased the activation of PI3K/Akt-Nrf2 signalling in response to CS. Conclusions: BSFCF attenuated CS-induced inflammation in COPD, which was partially achieved through the PI3K/Akt-Nrf2 and NF-κB signalling pathways. Graphical abstract: Image 1